A condição de refúgio no Brasil: políticas de ações afirmativas no trabalho e no ensino superior público paulista - Guilherme, Maria Luiza Cavazotto (Universidade Federal de São Carlos, 2021)
This paper aimed to understand the condition/state of refuge in Brazil, from its socioeconomic profile with interface in the fields of labor, health and education. The general objective of the research was to problematize and describe the condition of people in a refuge state or forced migration in Brazil, based on affirmative actions policies in the affirmative actions field of higher education in São Paulo's universities. Based on the methodology of fundamental bibliographical type, the research conducted an in-depth analysis of specific studies on actions in the labor, health and education areas and at the same time, of the edicts of five chosen São Paulo's public universities: Unicamp, UFSCar, UFABC, USP and UNIFESP, to examine the affirmative actions thought for refugees in each of them. Within the limits of this research, it is concluded that the government is one of the essential pillars to ensure the reception of people in a state of refuge, at the same time, it highlights the actions of student movements and other organizations that seek to awaken affirmative actions for this population.
The refuge condition in Brazil: affirmative action policies at work and in public higher education in São Paulo
Keywords: Pessoas em estado de refúgio; Universidades públicas paulistas; Políticas de ações afirmativas; Trabalho; People in a state of refuge; Public universities in São Paulo; Affirmative actions policies; Labor; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO